Pemberdayaan Masyarakat Pemberdayaan Masyarakat Desa Noelbaki Melalui Pemanfaatan Tanaman Lokal Menjadi Sediaan Handsanitizer Pada Masa Pandemi Covid-19 - I Gusti Made Budiana; Jakobis Johanis Messaks; Luh Putu Ruliati (Universitas Nusa Cendana, 2023)
Abstract Currently, Indonesia is facing the 3rd wave of Covid-19 attacks. Especially in the city of Kupang, almost 90% of the area has a red zone status. The Government's response to the above pandemic problem is to break the chain of the spread of Covid-19 in line with government policies (Ministry of Health and Ministry of Disadvantaged Villages) including increasing knowledge and changing community behavior, implementing clean and healthy lifestyles and issuing village or sub-district preparedness policies to face Covid-19 pandemic. Noelbaki Village is one of the villages in Kupang Regency, NTT Province which has a wealth of local plants that can be used to break the chain of the spread of COVID-19. who are vulnerable to the spread of COVID-19, so it is necessary to take anticipatory steps to protect the community in preventing and breaking the chain of the spread of this disease. The objectives to be achieved from this Community Service activity are: The community is able to use local plants as an effort to improve the body's immune system, the community is able to make hand sanitizer and household-scale disinfectant from local plants (betel leaf, aloe vera, orange) as an effort to maintain health and break the chain of spread of Covid-19 and other infectious diseases. The stages of this service activity are as follows; (1) exploration of partners, (2) processing of permits for the implementation of service activities, (3) implementation of training for the people of Noelbaki Village, (3) Publication and Reporting. The results of the service activities showed that the people of Noelbaki Village, which were dominated by women, were very enthusiastic about participating in the activities. The products produced are booster drinks (immune boosters), hand sanitizers and disinfectants. Key words: Hand Sanitizer, disinfectant, covid-19, prevention Abstrak Saat ini Indonesia menghadapi serangan Covid-19 gelombang ke-3. Khususnya di Kota Kupang sudah hamper 90% wilayahnya sudah status zona merah. Respon Pemerintah terkait masalah pandemi diatas dengan upaya memutus mata rantai penyebaran Covid-19 sejalan dengan kebijakan pemerintah (Kementerian Kesehatan dan Kementerian Desa Tertinggal) diantaranya dengan meningkatkan pengetahuan dan perubahan perilaku masyarakat, menerapkan pola hidup bersih dan sehat dan mengeluarkan kebijakan kesiapsiagaan desa atau kelurahan menghadapi pandemik Covid-19. Desa Noelbaki merupakan salah satu desa di kabupaten Kupang Provinsi NTT yang memiliki kekayaan tanaman lokal yang dapat dimanfaatkan untuk memutus mata rantai penyebaran covid-19. yang rentan terhadap penyebaran covid-19 sehingga perlu dilakukan langkah antisipasi untuk menjaga masyarakat dalam mencegah dan memutus mata rantai penyebaran penyakit ini. Tujuan yang ingin dicapai dari kegiatan Pengabdian Masyarakat ini adalah : Masyarakat mampu memanfaatkan tanaman lokal sebagai upaya meningkatkan sistem imun tubuh, Masyarakat mampu membuat Hand Sanitizer dan Desinfektan skala rumah tangga dari tanaman lokal (daun sirih, lidah buaya, jeruk) sebagai upaya menjaga kesehatan dan memutus mata rantai penyebaran Covid-19 dan penyakit menular lain.Tahapan kegiatan pengabdian ini adalah sebagai berikut; (1) penjajakan mitra, (2) pengurusan surat izin pelaksanaan kegiatan pengabdian, (3) pelaksanaan pelatihan bagi masyarakat Desa Noelbaki, (3) Publikasi dan Pelaporan. Hasil kegiatan pengabdian menunjukkan bahwa masyarakat Desa Noelbaki yang didominasi oleh ibu-ibu sangat antusias mengikuti kegiatan. Produk yang dihasilkan berupa minuman booster (penguat imun tubuh), hand sanitizer dan desinfektan. Kata-kata kunci: Hand Sanitizer, desinfektan, covid-19, pencegahan